2018
DOI: 10.1007/s11250-018-1533-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reproductive disorders on productivity and reproductive efficiency of dromedary she-camels in relation to cytokine concentration

Abstract: This experiment was conducted to study the effect of reproductive disorders on reproductive efficiency and milk production in relation with pro-inflammatory cytokines in dromedary she-camels. Total of 20 late pregnant Maghrabi she-camels, aging 6-9 years, weighing 420-550 kg, and between the second and third parities were divided into two groups. Animals in the first group (n = 12) showed normal reproductive status (G) at parturition, while those in the second one (n = 8) were suffered from reproductive disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Cytokines play an important role in innate immunity, apoptosis, angiogenesis, cell growth and differentiation. Cytokines are also involved in the process of most diseases including cancer 47,48 and reproduction disorders 23,49,50 . It has reported that proinflammatory cytokines could affect BTB permeability and enter into the seminiferous tubules to induce apoptosis of germ cells 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines play an important role in innate immunity, apoptosis, angiogenesis, cell growth and differentiation. Cytokines are also involved in the process of most diseases including cancer 47,48 and reproduction disorders 23,49,50 . It has reported that proinflammatory cytokines could affect BTB permeability and enter into the seminiferous tubules to induce apoptosis of germ cells 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies investigated the changes in the camel leukogram pattern under different physiologic (age, sex, pregnancy) (63)(64)(65) and pathologic (infection) conditions (66,67). As most camel leukogram studies presented leukocyte composition as relative values (fractions) rather than absolute values, it is difficult to compare the results obtained from different studies.…”
Section: The Leukogram Pattern Of Camels In Health and Diseasementioning
confidence: 99%
“…In She Camel, iodine supplements at a level of 1 mg/kg significantly improved the reproductive performance of lactating camels, as measured by the shortest time of the first heat onset; days open (DO), the number of services per conception (NSC), time of placental drop, uterine involution, and the calving interval. Iodine treatment also yielded the highest conception rate [24].…”
Section: Mineralsmentioning
confidence: 91%